Nanocomposites of waterborne polyurethane reinforced with cellulose nanocrystals from sisal fibres - Mondragón, G. (2017)
Cellulose nanocrystals (CNC) were isolated from sisal fibres and were incorporated in the form of an aqueous suspension to a waterborne polyurethane (WBPU) synthesized from components derived from natural sources using an aliphatic diisocyanate. Transparent nanocomposite films with different CNC contents were prepared using a casting method. The morphology, thermal behaviour and mechanical properties of the nanocomposite films were characterized. Homogeneous distribution of CNC in the WBPU, even at high CNC contents was observed, resulting in an increase of 100% in modulus for systems with 5 and 10 wt% of CNC, with high elongations around 650%.